Concrete structures durability and repair - Sahafnia, Mahdi (Kansas State University, 2018)
Reinforced concrete exceptional durability is a major reason why it is the most popular structural material in many infrastructures around the world. Most concrete structures serve for several decades; therefore problems of concrete durability gradually arise. To insure that concrete structures perform functionally, it is necessary to maintain and inspect them regularly. The durability of the reinforced concrete structures generally depends on four major factors: structure design and construction, maintenance, concrete aggregates, and environmental conditions. The most common causes of concrete deterioration are carbonation, design and construction errors, alkali-aggregate reactions, freeze-thaw cycles, and corrosion. Each type of concrete deterioration has its own signs and characteristics. Choosing the best repair technique to address concrete deterioration requires specific analysis and tests to find the cause of the deterioration and the extent of the damage. This study analyzes concrete structures inspection techniques to recognize the source of the problem and the part of the structure which has been affected. Choosing the most proper repair and strengthening techniques to prevent the structure from getting exposed to any further environmental and chemical are the next steps.
Keywords: Concrete durabilityConcrete